Proof That Chronic Lyme Disease Exists - Cameron, Daniel J. (Interdisciplinary Perspectives on Infectious Diseases, 2010)
The evidence continues to mount that Chronic Lyme Disease (CLD) exists and must be addressed by the medical community if solutions are to be found. Four National Institutes of Health (NIH) trials validated the existence and severity of CLD. Despite the evidence, there are physicians who continue to deny the existence and severity of CLD, which can hinder efforts to find a solution. Recognizing CLD could facilitate efforts to avoid diagnostic delays of two years and durations of illness of 4.7 to 9 years described in the NIH trials. The risk to society of emerging antibiotic-resistant organisms should be weighed against the societal risks associated with failing to treat an emerging population saddled with CLD. The mixed long-term outcome in children could also be examined. Once we accept the evidence that CLD exists, the medical community should be able to find solutions. Medical professionals should be encouraged to examine whether: (1) innovative treatments for early LD might prevent CLD, (2) early diagnosis of CLD might result in better treatment outcomes, and (3) more effective treatment regimens can be developed for CLD patients who have had prolonged illness and an associated poor quality of life.